Ritual sites and religious rivalries in late Roman North Africa - Lander, Shira L. (Cambridge ; New York)
xvii, 253 sayfa
Keywords: “In Ritual Sites and Religious Rivalries in Late Roman North Africa, Lander examines the rhetorical and physical battles for sacred space between practitioners of traditional Roman religion, Christians, and Jews of late Roman North Africa. By analyzing literary along with archaeological evidence, Lander provides a new understanding of ancient notions of ritual space. This regard for ritual sites above other locations rendered the act or mere suggestion of seizing and destroying them powerful weapons in inter-group religious conflicts. Lander demonstrates that the quantity and harshness of discursive and physical attacks on ritual spaces directly correlates to their symbolic value. This heightened valuation reached such a level that rivals were willing to violate conventional Roman norms of property rights to display spatial control. Moreover, Roman Imperial policy eventually appropriated spatial triumphalism as a strategy for negotiating religious conflicts, giving rise to a new form of spatial colonialism that was explicitly religious“ -- Yayıncı.